Association of Vitamin D Intake in Pregnant Women and Birth Weight - Cindy Rolexza; Fathia Meirina (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: Insufficient maternal consumption of vitamin D can have adverse effects on fetal development and increase the likelihood of low birth weight. This research aimed to establish the correlation between the quantity of vitamin D consumed by expectant mothers and the weight of newborns. Methods: This study utilized an analytical observational design with a cross-sectional approach, collecting data from August to November 2022. Information on Vitamin D intake and birthweight was obtained via questionnaire interviews with 96 pregnant women delivering at the University of North Sumatera Hospital or Maharani Women’s and Children Hospital. Semi-Food Frequency Questionnaires (FFQs) served as the data collection instrument. Non-probability consecutive sampling was employed. Statistical techniques, including Chi-square and Fisher's Exact test, were used for data analysis. Findings indicated a prevalence of inadequate vitamin D intake among mothers (3.125%). The mean daily consumption of vitamin D among expectant women was 19.99 μg/day. Mother's education level did not significantly influence the outcome (p=0.589). Results: The results of this study suggest that there was no significant association between maternal age at pregnancy (p=0. 135), gestational age (p=0. 771), parity (p=0958), and baby's sex (p=0. 448) with birth weight. Conclusion: An observed association existed between the prenatal intake of vitamin D and neonatal birth weight in expectant mothers.